Nutritional Composition of Momordica dioica fruits: As a wild vegetable - Salvi, Jyotsna (Journal of Food and Pharmaceutical Sciences, 2015)
Samples of Momordica dioica Roxb. ex Willd fruits were collected from Jhadol Tehsil of southern Rajasthan. The fruits were washed, ground into powder and analyzed for the proximate, vitamins, mineral and Fatty acid compositions. The values (% DW) of moisture, ash, crude protein, crude fiber, crude fat and carbohydrate available were 87, 14, 52.06, 15.36, 4 and 14.58, respectively. Levels (g/100g DW) of vitamins A, B1, B2, B6, H and K were 2.5, 1.8, 3.5, 4.3, 6.5 and 15 respectively. The values (mg/100g DW) of minerals potassium, sodium, calcium, zinc, Copper and magnesium were 370, 58, 26000, 8.5, 1.7 and 14000 respectively. Comparing the mineral and vitamin composition with recommended dietary allowances (RDA), the result indicated that Momordica dioica fruits could be good supplement for vitamin B1, B2, B6, B9, Ca and Mg. The values (% DW) of fatty acids i.e. Oleic acid, Palmitic acid, Linoleic acid, Myristic acid and Stearic acid of fruits were 56.253, 12.157, 22.511, 3.589 and 3.547 respectively.Â  The results indicated that Momordica dioica fruits could be a good supplement for some nutrients, minerals and fatty acids such as fiber, protein, carbohydrates, calcium, magnesium, Oleic acid, and Linoleic acid. The fruit could be promoted as a mineral and vitamin supplement for cereal-based diets in poor rural communities.Â